Implementation of Information System and Software Quality Testing in Company Operational Applications Based on ISO/IEC 25010 (Case Study: PT Snapdev Digital Indonesia) - Chairul Anwar; Rahmat Hartono (Jurnal Teknologi Informatika dan Komputer, 2026)
Implementation of information system quality testing is an important factor in supporting the effectiveness and efficiency of company operations. This study aims to implement an information system and conduct software quality testing based on the ISO/IEC 25010 standard at PT Snapdev Digital Indonesia. Quality testing is carried out by measuring seven main characteristics, namely Performance Efficiency, Compatibility, Usability, Reliability, Security, Maintainability, and Portability. The research methods used include observation, data collection, and analysis of test results based on indicators in each ISO/IEC 25010 characteristic. The measurement results show that the percentage value for each aspect of system quality is in the range of 79%–83%, which indicates that the system has met most of the established quality criteria. The overall average value of 80.97% places the system quality in the very good category. This indicates that the system has efficient performance, adequate levels of security and reliability, good ease of use, and can be maintained and run in various environments. However, there are still opportunities for improvement in several aspects to improve system quality to be more optimal. Overall, the implemented information system is considered suitable for use and complies with international software quality standards.